Extraction, Antioxidant Activity and HPLC Study of Bioactive Compound Present in Leaves Extract of Onosma Bracteatum - Vishnukant Kamble, Subodh; Soni, Prashant (Journal of Neonatal Surgery, 2025)
The leaves of Onosma bracteatum, a member of the Boraginaceae family, are known for their medicinal properties, which are attributed to the presence of bioactive compounds such as flavonoids and phenolic acids. This study aims to investigate the antioxidant activity and bioactive compound profile of the ethanolic extract of Onosma bracteatum leaves, using DPPH and nitric oxide (NO) inhibition assays, along with High-Performance Liquid Chromatography (HPLC) for the quantification of key compounds. The DPPH and NO assays revealed that the ethanolic extract exhibited significant antioxidant activity, although not as potent as ascorbic acid. The IC50 values for the DPPH and NO assays were 75.62 µg/ml and 83.39 µg/ml, respectively. HPLC analysis identified quercetin and gallic acid as the major bioactive compounds in the extract, with 0.831% quercetin and 0.940% gallic acid. The results suggest that Onosma bracteatum leaves are a valuable source of natural antioxidants, which could have potential therapeutic applications in the treatment of oxidative stress-related diseases. Further studies are needed to explore the full range of pharmacological properties and possible clinical uses of this plant.